Description and biology of two new egg parasitoid species (Hymenoptera: Trichogrammatidae) reared from eggs of Heliconiini butterflies (Lepidoptera: Nymphalidae: Heliconiinae) in Panama. Issue 11 (27th March 2019) - Woelke, Jozef B.; Fursov, Viktor N.; Gumovsky, Alex V.; de Rijk, Marjolein; Estrada, Catalina; Verbaarschot, Patrick; Huigens, Martinus E.; Fatouros, Nina E.
ABSTRACT: Two new minute egg parasitoid wasp species belonging to the genus Trichogramma (Hymenoptera: Trichogrammatidae), T. chagres sp. nov. and T. soberania sp. nov., were found in a tropical lowland rainforest in Panama, Central America. In this paper, we describe, illustrate and discuss the biology and morphological and molecular characterization of the two new Trichogramma wasp species. Both species were collected from eggs of passion vine butterflies, Agraulis vanillae vanillae (Lepidoptera: Nymphalidae: Heliconiinae) and unidentified Heliconiini species, laid on different Passiflora species (Malpighiales: Passifloraceae). A female T. soberania sp. nov. wasp was observed on the wings of a female Heliconius hecale melicerta butterfly caught in the wild. This suggests that this species may occasionally be phoretic on adult female butterflies to find suitable host eggs. Our study adds two more species identifications to the scarce record of Trichogramma wasps from the widespread Heliconiini butterflies in Central America. urn:lsid:zoobank.org:pub:941854EE-4A47-4A98-B88E-1EC19D83D074